EPIDEMIOLOGICAL FEATURES OF TOXOPLASMOSIS IN AZERBAIJAN - M. K. Musaeva (Сеченовский вестник)
This article deals with the problems of parasitic diseases, with the analysis of epidemiological features of toxoplasmosis in Azerbaĳan.